An intertextual analysis on readers' comments in Malaysiakini and Free Malaysia Today : a case study on the news of the formation of Parti Pribumi Bersatu Malaysia - Dayang Mahani Jafri (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study applies the intertextual analysis research method to examine readers' comments in selected online news portals, Malaysiakini and Free Malaysia Today (FMT), pertaining to the issue on the formation of Parti Pribumi Bersatu Malaysia (PPBM). The study aims to investigate the discourse practices of Malaysian readers by unraveling the implicit messages in their comments. Intertextual analysis method is adapted from Fairclough's (2001) three-dimensional framework. A total of 80 comments were extracted from selected online news portals for this study which dated from the beginning of August 2016 until the end of September 2016. The comments were then categorised into two groups labelled as 'propaganda marker' and 'constructive criticism' with 20 comments each. Based on the data analysis on readers' comments, the findings reveal that the comments posted are related to the articles. The propaganda makers are those who are either pro-government or pro-opposition or fence-sitters. Meanwhile, constructive critics are referred to those who are neutral in their views but prefer to propagate unity and equality in the country. The findings of the study indicate that the discourse practices and social realities of Malaysian readers in FMT and Malaysiakini are discursively constructed. It also corroborates with previous Critical Discourse Analysis (CDA) studies conducted on readers' comments on online news portals. Hence, this study contributes to the field of CDA, especially in highlighting intertextual analysis as a reliable method to examine the language usage and to investigate the discourse practices of the readers.